The Lamb and the Butterfly - Sundgaard, Arnold 1909-2006.; Carle, Eric (New York : Orchard Books, 2013)
A protected lamb and an independent butterfly discuss their different ways of living.
aReprint. Originally published: 1988.
Keywords: Sheep -- Fiction; Butterflies -- Fiction; Individuality -- Fiction